Artaud: La véritable histoire d'Artaud le Mômo - Mordillat, Gérard; Prieur, Jérôme (France Arte France, 2005)
et. Actor. Director. Philosopher. Visionary. Madman. All of these words describe Antonin Artaud (1896-1948), who remains one of the most influential figures in 20th century art, theater, and cinema. His influence is evident in the works of such theater luminaries as Jean Genet, Fernando Arrabal, Peter Weiss, and Peter Brook, and extends into the world of rock n roll through artists like Jim Morrison and Patti Smith. ARTAUD is an amazing 2-DVD set that sheds light on the enigmatic genius who penned The Theater and Its Double, one of the theaters sacred texts, and whose "Theater of Cruelty" manifesto cast a giant shadow over the development of theater in the 20th century. Artaud is also well known for his brilliant performance in early classics of world cinema, including Abel Gances Napoleon and Carl Th. Dreyers The Passion of Joan of Arc. The two discs in this set include: MY LIFE AND TIMES WITH ANTONIN ARTAUD Following the final years of Artauds life after his rescue from Rodez Asylum by friends and followers, My Life and Times with Antonin Artaud features an amazing performance by Sami Frey (Black Widow, Family Life) in the title role. The films moody black-and-white photography perfectly evokes the disillusionment of post-WWII Paris. THE TRUE STORY OF ARTAUD THE MOMO